Pregnancy outcomes after spontaneous conception with previous spontaneous abortion preceding present pregnancy - Dadheech, Shree Kant; Bharadwaj, Meenakshi K.; Menon, Brig Aruna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of the present study was to study pregnancy outcomes in patients with Spontaneous conception with history of previous spontaneous abortion preceding present pregnancy. Methods: A prospective study included patients with spontaneous conception with history of previous spontaneous abortion preceding present pregnancy admitted in the department of obstetrics and gynecology, command hospital, Pune between October 2018 and April 2020. The patients were booked (minimum 3 visits in antenatal outdoor clinic) or admitted for the first time as an emergency. The detailed history about previous abortions was taken and routine as well as investigations for possible etiologies of previous abortions were done. Cases with history of mid-trimester abortion were investigated for cervical incompetence. All the patients were observed for complications during present pregnancy like threatened abortion, preeclampsia, preterm labour, intrauterine death and final outcome. Results: A total of 110 patients with history of previous spontaneous abortion were admitted, all patients were booked. Majority (51.8 %) of patients belong to the age group 25-30 years. All patients were with history of previous one abortion followed by pregnancy with spontaneous conception. The final outcomes were term live birth (86.4%), abortion (8.2%), preterm delivery (5.4%), and no still birth. Caesarian section was done in 32.7% patients for various indications. Conclusions: Previous history of spontaneous abortion is associated with adverse pregnancy outcome. There is increased risk of abortion, preterm delivery, need for caesarean sections and fetal loss in cases of previous spontaneous abortions. These complications and fetal loss can be reduced by booking the patients and giving due antenatal care.